Procedures to obtain enviromental surveying | Procedimentos para obtenção de levantamento ambiental - Machado, José (Revista Geama, 2016)
The man has gone through several evolutionary processes of survival throughout history from its primary forms to the current settings of society. The first people of prehistory were nomads who had no fixed residence and survived by hunting, fishing and plant extraction . Over time , there was the need for human survival change habits , for the food , which until then only exploited , were getting scarce , going to have a fixed residence and becoming a sedentary species. He learned to grow their own food and raise animals , emerging then , agriculture and livestock, thus forming more complex societies , such as towns and cities. Planimetric survey are various surveying procedures, without considering the relief, seeking the graphical representation of a land area by obtaining necessary elements as angles, distances, geographic location and position or orientation. The aim of work is inform the more important procedures to obtain environmental surveying.